IMPLEMENTASI METODE SYSTEM USABILITY SCALE DAN HEURISTIC EVALUATION DALAM EVALUASI APLIKASI SI PAWANG DI KECAMATAN NGAJUM KABUPATEN MALANG - Mita Septiana Damayanti; Weda Adistianaya Dewa; Indah Dwi Mumpuni (Prodi Teknik Informatika, Fakultas Sains dan Teknologi, 2025)
The Personnel Information System (SI PAWANG) in Ngajum District was developed to make it easier to manage personnel data digitally. The aim of this research is to assess SI PAWANG using two methods, namely the System Usability Scale (SUS) and Heuristic Evaluation (HE). The SUS method is applied to measure user satisfaction through questionnaires distributed to employees who use the system. The evaluation results show that the SUS score for SI PAWANG is 69.85, which is included in the